Family members of detainees and human rights lawyers: trajectories in the construction of a public cause - Pereyra Iraola, Victoria (2017)
In Argentina, social activism around claims for justice that are initiated by those who publicly present themselves as family members of those who have suffered or suffer some kind of harm, has a long history. The Asociación Civil de Familiares de Detenidos en Cárceles Federales (ACIFAD) is formed mainly by mothers, partners, daughters and sisters of prison detainees. They actively collaborate with a group of lawyers and professionals from the Centro de Estudios de Política Criminal and Human Rights (CEPOC). In this article, we focus on the career paths undertaken by the leaders of both associations to illustrate the symbolic construction through which they contribute to the public recognition of the family members of those detained as a particular social collective. While contributing to the social existence of these group, these women recognize themselves and gradually attain recognition as spokeswomen of the situation of detainees families.